A prospective study of carpal tunnel syndrome: workplace and individual risk factors. Issue 8 (20th June 2013) - Burt, Susan; Deddens, James A; Crombie, Ken; Jin, Yan; Wurzelbacher, Steve; Ramsey, Jessica
Abstract : Objectives: To quantify the risk for carpal tunnel syndrome (CTS) from workplace physical factors, particularly hand activity level and forceful exertion, while taking into account individual factors including age, gender, body mass index (BMI), and pre-existing medical conditions. Methods: Three healthcare and manufacturing workplaces were selected for inclusion on the basis of range of exposure to hand activity level and forceful exertion represented by their jobs. Each study participant's job tasks were observed and evaluated onsite and videotaped for further analysis, including frequency and duration of exertion and postural deviation. Individual health assessment entailed electrodiagnostic testing of median and ulnar nerves, physical examination and questionnaires at baseline with annual follow-up for 2 years. Results: The incidence of dominant hand CTS during the study was 5.11 per 100 person-years (29 cases). Adjusted HRs for dominant hand CTS were as follows: working with forceful exertion ≥20% but <60% of the time: 2.83 (1.18, 6.79) and ≥60% of the time vs <20%: 19.57 (5.96, 64.24), BMI ≥30 kg/m 2 (obesity): 3.19 (1.28, 7.98). The American Conference for Governmental Industrial Hygienists (ACGIH) Threshold Limit Value (TLV) for hand activity level also predicted CTS, HR=1.40 (1.11, 1.78) for each unit increase in the TLV ratio, controlling for obesity and job strain. Conclusions: Workplace and individual risk factors both contribute to the risk for CTS. Time spent in forceful exertion can be a greater risk for CTS than obesity if the job exposure is high. Preventive workplace efforts should target forceful exertions.